FORENSIC ODONTOLOGY AND DENTAL STATUS OF ADULT PATIENTS ATTENDING THE OUT PATIENT DENTAL DEPARTMENT OF A TERTIARY CARE HOSPITAL - Seema, Nighat; Ahmed, Iftikhar; Shireen, Fatima; Rafiq, Anam; Khan, Najia Sajjad; Jadoon, Omair Khan (Journal of Ayub Medical College Abbottabad, 2019)
Background: Pakistan is one of the countries where practice of forensic odontology and its record keeping is poor due to which we face difficulty in identification of individuals in disasters and other medicolegal problems. The objectives of this study were to know the status of forensic odontology and to determine the dental status of adult patients attending dental outpatient department of Ayub Teaching hospital Abbottabad. Methods: A cross-sectional Study was carried out from 1st September to 30th September 2018 in the Department of Dentistry, Ayub Teaching Hospital, Abbottabad. A questionnaire was designed including preliminary record, standard dental chart, notation chart and other variables. A sample of 96 patients having all permanent teeth were included and examined. Non-probability convenience sampling was used. Data was collected and analyzed on SPSS. Results: The sample consisted of 59.4% males and 40.6% females. Mean number of present teeth with sound status was 24±5. Faulty development was found in 14.6% of the patients. Faulty alignment, black/brown stains and attrition were observed in 38.5%, 86.5% and 25% of the patients respectively. No statistically significant association was found (p >0.05) between gender and faulty development, faulty alignment, staining or attrition. Forensic odontological practice and its record are not maintained in the hospital. Conclusions: High proportion the patients have black/brown stains. Faulty alignment is more as compared to faulty development. In our study we observed that no odonatological record is maintained in our hospital. Keywords: forensic odontology; identification; cross bite; overbite